SYSTEMS APPROACH TO SUCCESSFUL CO-OPERATIVE ENTERPRISE DEVELOPMENT IN KENYA - Akomo, Ouma Caren (European Scientific Journal, ESJ, 2015)
This is a desk researched paper which starts with an introduction to systems approach by incorporating the understanding to the approach. The paper proposes an expert system approach that incorporates Quality Function Deployment (QFD) methodology for the identification of the strategic components of a Co-operative Society for a Product Data Management (PDM) system. An understanding of the systems approach is elaborated according to the phases which a system is expected to go through. The current systems approach to successful Co-operative enterprises in Kenya is explained. This has been done by noting three major components, namely; formation of the co-operative enterprise detailing what it takes for such enterprises to be formed, the management of the co-operative enterprises indicating the three major organs in the management( members, officials and staff), and the government with its two major roles, that is the promotion and the legal functions. The paper has proposed a conceptual framework for the successful co-operative enterprise development in Kenya. Further, the paper has elaborated on the various factors which should be considered for successful co-operative enterprises in Kenya. In the last chapter of this paper, there are some suggestions for the various factors that should be taken into account if the proposed model is to be implemented.